Formation and Activation of Zr/Hf Bis(phenolate‐ether) Precatalysts. Issue 29 (29th July 2019) - Cuthbert, Eric N. T.; Busico, Vincenzo; Herbert, David E.; Budzelaar, Peter H. M.
Abstract : Zr and Hf complexes of bis(phenolate‐ether) ("O4") ligands feature high activity, stereoselectivity and molecular weight capability for propene polymerization at high temperature. Here we report a simplified ligand synthesis and several new examples of O4 ligands. The formation of precatalysts L MR2 (M = Zr, Hf; R = Bn, Me) from L H2 and MR4 was found to be accompanied in some cases by the formation of dimers (µ‐L)2 [MR2 ]2, and X‐ray structures of two such dimers have been determined. Treatment of L MMe2 with [Ph3 C] + [B(C6 F5 )4 ] – produces fairly clean cationic species L MMe + which were studied by 1 H NMR. 2D ROESY data, in particular, suggest that for "smaller" O4 ligands the L MMe + cation reversibly rearranges from the active ( fac/fac ) form to a presumably inactive fac/mer or mer/mer form; more bulky substituents appear to suppress this rearrangement. Implications for polymerization catalysis are discussed. Abstract : Catalyst formation can be less than straightforward. Bis(phenolate‐ether) ligands are shown to form not only monomeric complexes LMR2 (M = Zr or Hf) but also bridged dimers (µ‐L)2 [MR2 ]2 . Moreover, NMR studies indicate that activated catalysts LMMe + are involved in conformational equilibria.